Utilization of Tamarind Seed Biocoagulant as Learning Material for Water Purification Practicum in Colloidal System - Dhi Ayu Wulan Septiya; Laili Nailul Muna (IKIP Mataram, 2024)
Discharging wastewater directly into the environment can harm nearby organisms. Efforts to increase environmental awareness, especially about sewage, can be started with educational activities. The study investigates the correlation between chemistry material and water purification using tamarind seed bio coagulant, assessing its feasibility for chemistry experiment design in schools. This research uses descriptive qualitative research. This study described data from observations of water purification using tamarind seedcoagulant, literature studies on chemistry practicum, and interviews with two chemistry teachers and two high school students.The results showed that the relationship between colloidal material and the experiment was to determine the types of products that contain colloidal systems in daily life and the properties of colloids. The results of the chemical parameter test revealed significant changes in the pH levels of river, laundry, and batik wastewater samples, with batik coloring waste showing the most significant changes. The organoleptic test results revealed significant changes in the color, odor, and sediment of batik dyeing wastewater. The protein in tamarind seeds can destabilize substances that cause turbidity. Based on literature studies and interviews, tamarind seed bio coagulant is feasible as a teaching material for chemistry practicum on colloidal system.